Close contact TB disease status by index AFB smear grade exposure. - Rehan R. Syed (14126286) (2024)
The proportions of index participant baseline AFB smear grades are shown by progression status. “N/S” denotes a negative or scanty smear grade. Close contacts for whom the corresponding index AFB smear status was not available have been omitted (non-progressor n = 744, progressor n = 21, co-prevalent n = 10). Progression to TB disease among close contacts, either with progressor or co-prevalent status, was not found to be related to their index participant’s baseline AFB smear grades (Fisher’s exact p = 0.791).